Abnormal Shift in B Memory Cell Profile Is Associated With the Expansion of Circulating T Follicular Helper Cells via ICOS Signaling During Acute HIV-1 Infection - Lu, Xiaofan; Zhang, Xin; Cheung, Allen Ka Loon; Moog, Christiane; Xia, Huan; Li, Zhen; Wang, Rui; Ji, Yunxia; Xia, Wei; Liu, Zhiying; Yuan, Lin; Wang, Xiuwen; et al. (Frontiers in Immunology, 2022)
Interactions between T follicular helper (Tfh) cells and germinal center B cells are essential for the differentiation of B cells and specific antibody responses against HIV-1 infection. However, the extent to which HIV-1 infection affects the dynamic interplay between these two cell populations in the bloodstream remains unclear. In this study, the dynamics of circulating Tfh (cTfh) and B cells and their relationship in individuals with acute and chronic HIV-1 infection were investigated. Twenty-five study subjects were enrolled from the Beijing PRIMO clinical cohort, a prospective cohort of HIV-1-negative men who have sex with men (MSM) for the identification of cases of acute HIV-1 infection (AHI) at Beijing Youan Hospital, Capital Medical University. Individuals with AHI were selected at random. Matched samples were also collected and analyzed from the same patients with chronic HIV-1 infection. None of the study subjects received antiretroviral therapy during acute or chronic infection. Multicolor flow cytometry was used for the immunophenotypic and functional characterization of cTfh cell and B cell subsets. AHI resulted in increased proportions in bulk cTfh, ICOS+cTfh or IL-21+ICOS+cTfh cells. In both acute and chronic infections, activated memory (AM), tissue-like memory (TLM), and plasmablast (PB) B cell levels were increased whilst resting memory (RM) and naïve mature (NM) B cell levels were decreased. Classical memory (CM) B cells were unaffected during infection. Association analyses showed that the levels of ICOS+cTfh and IL-21+ICOS+cTfh cells were negatively correlated with those of AM, CM, RM cells, and positively correlated with those of NM cells in AHI but not chronic HIV-1 infection stage (CHI). Moreover, the frequency of IL-21+ICOS+cTfh cells was also positively correlated with plasma HIV-1 viral load, and had an opposite association trend with CD4+T cell count in AHI. Our data suggests that HIV-1 infection drives the expansion of cTfh cells, which in turn leads to perturbations of B cell differentiation through ICOS signaling during acute infection stage. These findings provide insight on the role of ICOS in the regulation of cTfh/B cell interaction during AHI and may potentially guide the design of effective strategies for restoring anti-HIV-1 immunity in the infected patients.